1976
DOI: 10.1111/j.1749-6632.1976.tb43368.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Regression of Advanced Atherosclerosis in Experimental Animals and Man*

Abstract: In general, the results to date in humans and experimental animals seem to indicate that substantial regression of advanced atherosclerosis is possible. The results also indicate that the advanced atherosclerotic lesions are much more likely to respond favorably if the serum cholesterol concentrations are reduced to the minimum that prevails in animals or people who consume a low-fat low-cholesterol diet. In human subjects and in rhesus monkeys, this value appears to be about 150 mg%. Under these circumstances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
3

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(45 citation statements)
references
References 20 publications
0
42
0
3
Order By: Relevance
“…Previous studies of atherosclerotic plaque progression and regression have revealed the dynamic nature of atherosclerotic lesions and the important role of macrophage neointimal trapping in lesion growth and macrophage emigration to regional lymph nodes in lesion regression (10,11,(30)(31)(32). The mechanisms involved in macrophage trapping in the inflamed atherosclerotic neointima are incompletely understood yet represent a novel target for potential therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of atherosclerotic plaque progression and regression have revealed the dynamic nature of atherosclerotic lesions and the important role of macrophage neointimal trapping in lesion growth and macrophage emigration to regional lymph nodes in lesion regression (10,11,(30)(31)(32). The mechanisms involved in macrophage trapping in the inflamed atherosclerotic neointima are incompletely understood yet represent a novel target for potential therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of factor VIII and vWF and of circulating immune complexes in the formation and evolution of the atherosclerotic lesions is unclear. However they promote concentric transmural plaques that lead to arterial dilatation and a tendency to thrombosis (8), with platelets, macrophages, granulocytes and lysosomal enzymes as mediators of the vessel damage.…”
mentioning
confidence: 99%
“…As suggested by Masoro (51), "...aging and atherosclerosis may merely share the same time frame, or there may be a causal interaction between them". Although animal studies have shown that intrinsic aging processes may enhance susceptibility to atherosclerosis (40,52), chemical analyses of arteries from specimens indicate that aging changes in extracellular matrix differ from those occurring with development of advanced atheroscierotic lesions (41,50). This suggests that atherosclerosis can be dissociated from the intrinsic aging of the arterial wall (50).…”
Section: Aging and Atherosclerosismentioning
confidence: 99%